Gambaran Usia Pernikahan Remaja (Studi Deskriptif Di Kecamatan Kasemen Kota Serang Provinsi Banten ) - Neisa Nisatul Hasanah (Perwakilan BKKBN Daerah Istimewa Yogyakarta, 2022)
This research is motivated by the number of teenage marriages in Kasemen District. The purpose of this study is to provide an overview of the marriage age of adolescents in Kasemen District in 2021. The method used is descriptive qualitative which describes data on age at first marriage, data obtained from interviews and data on Age at First Marriage (UKP) from the Office of Religious Affairs (KUA) of Kasemen District. The results of this study are a description of the marriage age of adolescents under the age of 20 in Kasemen District, Serang City. This happens because of several factors such as parents, education, economy, and oneself in Kasemen District, Serang City.